ABOUT A “BIBLICAL” TRIBE IN THE ART CONSCIOUSNESS OF M. GORKY AND I. BUNIN - I. S. Uryupin (Вестник Кемеровского государственного университета, 2015)
The paper focuses on the matter and functioning of the biblical culturonym/semantic image/eidos “Amalekites” in M. Gorky and I. Bunin's works. The concept is considered in a wide historical and cultural and religious and philosophical context, its historical, philosophical, mythological and poetic potential is revealed. The name of the tribe of Amalekites mentioned in the Old Testament and appealing to myths acquired an archetypic meaning in the cultural and philosophical consciousness of mankind; its semantic shades were appealed to in M. Gorky’s story “Former People” and in I. Bunin’s autobiographical novel “Arsenyev's Life”.